Effect of Applying Leakage Correction on rCBV Measurement Derived From DSC-MRI in Enhancing and Nonenhancing Glioma - Arzanforoosh, Fatemeh; Croal, Paula L.; van Garderen, Karin A.; Smits, Marion; Chappell, Michael A.; Warnert, Esther A. H. (Frontiers in Oncology, 2021)
Purpose: Relative cerebral blood volume (rCBV) is the most widely used parameter derived from DSC perfusion MR imaging for predicting brain tumor aggressiveness. However, accurate rCBV estimation is challenging in enhancing glioma, because of contrast extravasation through a disrupted blood-brain barrier (BBB), and even for non-enhancing glioma with an intact BBB, due to an elevated steady-state contrast agent concentration in the vasculature after first passage. In this study a thorough investigation of the effects of two different leakage correction algorithms on rCBV estimation for enhancing and non-enhancing tumors was conducted. Methods: Two datasets were used retrospectively in this study: 1. A publicly available TCIA dataset (49 patients with 35 enhancing and 14 non-enhancing glioma); 2. A dataset acquired clinically at Erasmus MC (EMC, Rotterdam, NL) (47 patients with 20 enhancing and 27 non-enhancing glial brain lesions). The leakage correction algorithms investigated in this study were: a unidirectional model-based algorithm with flux of contrast agent from the intra- to the extravascular extracellular space (EES); and a bidirectional model-based algorithm additionally including flow from EES to the intravascular space. Results: In enhancing glioma, the estimated average contrast-enhanced tumor rCBV significantly decreased (p<0.05, paired t-tests) across the patients, when applying unidirectional correction (from 4.64±2.14 to 4.43±2.08 in TCIA dataset; and from 3.29±1.86 to 2.88±1.68 in EMC dataset) or bidirectional correction (from 4.64±2.14 to 3.96±1.94 in TCIA dataset; and from 3.29±1.86 to 2.57±1.66 in EMC dataset). In non-enhancing glioma, a significant difference in observed rCBV was found only for bidirectional correction in the EMC dataset (from 1.4±0.6 uncorrected to 1.29±0.61 bidirectionally corrected). Conclusion: Both leakage correction algorithms were found to change rCBV estimation with BBB disruption in enhancing glioma, while there were limited effects in non-enhancing glioma. Stronger effects were found for bidirectional leakage correction than for unidirectional leakage correction.